Strengthening e-commerce in the Asia-Pacific region: Opportunities and challenges - J. Scott Marcus; Georgios Petropoulos; Toshiya Jitsuzumi (International Telecommunications Society (ITS), 2017)
What policy measures might contribute to greater use of e-commerce within the Asia-Pacific region, especially on a cross-border basis? What are the potential benefits, versus the potential costs? How feasible might it be to implement such measures? Surveys of consumers and merchants suggest that the Asia Pacific region is subject to challenges similar to those in Europe, where cross-border e-commerce has been a major policy focus for the past few years. We attempt in this paper to make a preliminary assessment of the applicability of European approaches to the strengthening of e-commerce in the Asia Pacific region.
Keywords: 330